2003
DOI: 10.1161/01.atv.0000074879.19006.51
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cyclooxygenases Inhibitors on Vasoactive Prostanoids and Thrombin Generation at the Site of Microvascular Injury in Healthy Men

Abstract: Objective-Balance between vasoactive prostanoids that contribute to homeostasis of the circulatory system can be affected by cyclooxygenases inhibitors. Results of a recent large clinical trial show that myocardial infarction was more frequent among patients with rheumatoid arthritis treated with the selective cyclooxygenase-2 inhibitor rofecoxib compared with those treated with naproxen. Whether this difference was attributable to deleterious cardiovascular effects of rofecoxib or cardioprotective effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Secondly, diclofenac and other NSAIDs have antiplatelet action, although its clinical significance is not determined [10,12,[18][19][20] . Additionally, diclofenac might affect platelet function in a cyclo-oxygenase-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, diclofenac and other NSAIDs have antiplatelet action, although its clinical significance is not determined [10,12,[18][19][20] . Additionally, diclofenac might affect platelet function in a cyclo-oxygenase-independent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In healthy volunteers, therapeutic doses of rofecoxib that are known to inhibit vascular PGI 2 production, do not result in significant changes in endothelial vasodilator responses [13]. In another clinical study, rofecoxib neither affected the levels of both PGI 2 and thromboxane A 2 metabolites, nor did it have an effect on bleeding time, platelet aggregation or thrombin generation after 7 days of treatment in an ex-vivo model of microvascular injury [14]. Further, internal mammary and radial arteries and saphenous veins donated by individuals with ongoing cardiovascular disease (during standard coronary artery bypass surgery) showed detectable levels of COX-1 but not COX-2 [15].…”
Section: Is Inhibition Of Prostaglandin Synthesis the Sole Mechanism mentioning
confidence: 96%
“…Tuleja et al [11] showed that the intensity of these differential effects is not the same for all NSAIDs.…”
Section: Case Reportmentioning
confidence: 98%